LAYANAN PENDIDIKAN AGAMA DI SMA (SLUA) SARASWATI 1 DENPASAR - Abdul Muin (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2015)
AbstractThis research aims at disclosing empirically with regard to general illustration of SMA Saraswati and religious education service against the student. This research data is collected by researcher through interview, observation, questionnaire and document. The research outcome shows: (1) Since the establishment in 1952, SMA Saraswati 1 has taught the religious education in accordance with religion they embrace and is taught by same religious teacher. Nevertheless, this school has not provided a special room for the student to perform worship in accordance with the religion. (2) All GPA has had academic qualification with background of religious education (link and match). (3) The religious service of Islam, Christian and Buddhist has not reached â€œideal qualityâ€ at this school.Â AbstrakPenelitian ini bertujuan untuk mengungkapkan secara empirik tentang gambaran umum SMA Saraswati dan layanan pendidikan agama terhadap peserta didik. Data penelitian ini dikumpulkan peneliti melalui wawancara, observasi, kuesioner dan dokumen. Hasil penelTitian ini menunjukkan: (1) SMA Saraswati 1 sejak berdiri 1952 telah mengajarkan pendidikan agama sesuai agama yang dianut peserta didiknya dan diajarkan oleh pendidik yang seagama. Namun, sekolah ini belum menyediakan tempat (ruang khusus) kepada peserta didik untuk melaksanakan ibadah sesuai agamanya. (2) Seluruh GPA telah memiliki kualifikasiÂ  akademik dengan latar belakang pendidikan guru agama (link and match). (3) Layanan pendidikan agama Islam, Kristen dan Buddha di sekolah ini, belum mencapai â€œkualitas idealâ€.